The Scientific and Societal Uses of Global Measurements of Subsurface Velocity - Szuts, Zoltan B.; Bower, Amy S.; Donohue, Kathleen A.; Girton, James B.; Hummon, Julia M.; Katsumata, Katsuro; Lumpkin, Rick; Ortner, Peter B.; Phillips, Helen E.; Rossby, H. Thomas; Shay, Lynn Keith; Sun, Charles; et al. (Frontiers in Marine Science, 2019)
Ocean velocity defines ocean circulation, yet the available observations of subsurface velocity are under-utilized by society. The first step to address these concerns is to improve visibility of and access to existing measurements, which include acoustic sampling from ships, subsurface float drifts, and measurements from autonomous vehicles. While multiple programs provide data publicly, the present difficulty in finding, understanding, and using these data hinder broader use by managers, the public, and other scientists. Creating links from centralized national archives to project specific websites is an easy but important way to improve data discoverability and access. A further step is to archive data in centralized databases, which increases usage by providing a common framework for disparate measurements. This requires consistent data standards and processing protocols for all types of velocity measurements. Central dissemination will also simplify the creation of derived products tailored to end user goals. Eventually, this common framework will aid managers and scientists in identifying regions that need more sampling and in identifying methods to fulfill those demands. Existing technologies are capable of improving spatial and temporal sampling, such as using ships of opportunity or from autonomous platforms like gliders, profiling floats, or Lagrangian floats. Future technological advances are needed to fill sampling gaps and increase data coverage.